(untitled) (International Journal of Built Environment and Sustainability, 2020)
The construction industry is vital to the economic development of any country. It has a major role in providing built infrastructures in an innovative and cost-effective way using an effective procurement approach. In contrast, the most widely used procurement method in Nigeria is the traditional procurement approach which is known for plaguing the industry with the poor working condition and poor performances thus, reducing the sustainability and quality of products and services. For this reason, there is a need for a procurement approach which utilises expertise to minimise the risk of non-performance and create a win-win environment for both client and contractors, while increasing transparency and add value to the project such like, the Best Value Procurement. Against the background, this paper aims to establish the perception of the Nigerian construction professionals on the unique factors of the Best Value Procurement. The paper outlines the following objectives: To identify the unique factors of the Best Value Procurement and, to establish the perception of the Nigerian construction professionals on the Best Value Procurement unique factors. Using a questionnaire survey, data was collected form 314 construction professionals involving Quantity Surveyors, Architects, Builders and Civil Engineers. Kruskal Wallis Test and mean score ranking was used for data analysis. The findings show that the professionals generally agree that the Best Value Procurement unique factors can bring about transparency, accountability, increase project performance and the contractor is the best to control risk and adds value to the project. This paper derives its significance from the need to stabilise the procurement system in Nigeria by transferring the risk and control to contractors who must act in the best interest of the client.